Synergistic effects of microplastics and ciprofloxacin co-contamination on arsenic bioaccumulation and microbial dysbiosis in rice soils: Implications for multi-pollutant agroecosystem risks - Wenlong Song; Xiaoxiao Zhang; Bing Ma; Lei Zhang (Environmental Chemistry and Ecotoxicology)
Soil contamination by arsenic (As), microplastics (MPs), and antibiotics poses significant risks to crop growth and food safety. However, the combined effects of MPs and antibiotics on As accumulation and microbial community structures in rice soils remain poorly understood. This study introduced polystyrene (PS), polyamide (PA), and ciprofloxacin (CIP) into soil microcosms to evaluate their individual and combined toxicological impacts on arsenate (As(V)), rice seedlings (Oryza sativa subsp. japonica Kato), and soil microbes. Both PS and CIP treatments inhibited chlorophyll production in rice while increasing plant biomass. Under combined contamination, chlorophyll content, biomass, root length, and shoot length were significantly lower than under individual treatments. Exposure to MPs and CIP also disrupted the antioxidant defense system in rice seedling leaves. Additionally, the presence of PS and PA improved soil physicochemical properties. However, the combined presence of MPs and CIP significantly reduced microbial diversity compared to individual contamination. At the phylum level, microbial composition remained consistent across treatments, whereas at the genus level, only Arthrobacter exhibited significant changes under individual treatments. In contrast, four genera were notably altered in soils co-treated with MPs and CIP. These findings highlight that the combined contamination of PS, PA, and CIP exacerbates the reduction of microbial diversity in As-contaminated soil.